Inovasi Pembelajaran Nilai-Nilai Kemuhammadiyahan untuk Membangun Peradaban Islam Modern - Aldi Ganda Kurnia Ganda Kurnia; Pickit Birahmatika; Syarifah Zainab Al Habsyi; Fachrizal Muttaqin; Lukmanul Hakim (Masterpiece: Journal of Islamic Studies and Social Sciences, 2026)
The development of information and communication technology has fundamentally transformed the landscape of da'wah and community empowerment. This research aims to examine the application of Muhammadiyah concepts in the context of the digital era, focusing on relevant core values, their implementation in realizing Progressive Islam, as well as the challenges and opportunities faced by Muhammadiyah. This study employs a qualitative approach with descriptive-analytical methods through library research on official Muhammadiyah documents, books, scientific journals, and relevant digital publications. Data analysis was conducted using content analysis methods through stages of data reduction, data presentation, and conclusion drawing with source triangulation techniques. The research findings indicate that the core values of Muhammadiyah relevant to the digital era include tajdid (renewal), rationality and ijtihad, amar ma'ruf nahi munkar, brotherhood and ukhuwah, as well as independence and community empowerment. The application of these values has been implemented through three strategic areas: digital da'wah transformation, education digitalization, and digital-based community economic empowerment. Muhammadiyah faces challenges including digital literacy gaps, competition of religious narratives, hoaxes and disinformation, as well as limited human resources. However, the digital era also opens strategic opportunities such as unlimited geographical reach of da'wah, organizational efficiency, and development of integrated digital ecosystems. This research recommends comprehensive strategies including the development of a digital transformation roadmap, human resource investment, digital infrastructure development, and strengthening of cybersecurity to enhance the implementation of Muhammadiyah concepts in the digital era. Abstraksi Perkembangan teknologi informasi dan komunikasi telah mengubah lanskap dakwah dan pemberdayaan umat secara fundamental. Penelitian ini bertujuan untuk mengkaji penerapan konsep kemuhammadiyahan dalam konteks era digital, dengan fokus pada nilai-nilai utama yang relevan, implementasinya dalam mewujudkan Islam Berkemajuan, serta tantangan dan peluang yang dihadapi Muhammadiyah. Penelitian ini menggunakan pendekatan kualitatif dengan metode deskriptif-analitis melalui studi kepustakaan terhadap dokumen resmi Muhammadiyah, buku, jurnal ilmiah, dan publikasi digital yang relevan. Analisis data dilakukan dengan metode analisis isi (content analysis) melalui tahapan reduksi data, penyajian data, dan penarikan kesimpulan dengan teknik triangulasi sumber. Hasil penelitian menunjukkan bahwa nilai-nilai utama kemuhammadiyahan yang relevan dengan era digital meliputi tajdid (pembaruan), rasionalitas dan ijtihad, amar ma'ruf nahi munkar, persaudaraan dan ukhuwah, serta kemandirian dan pemberdayaan umat. Penerapan nilai-nilai ini telah diimplementasikan melalui tiga bidang strategis: transformasi dakwah digital, digitalisasi pendidikan, dan pemberdayaan ekonomi umat berbasis digital. Muhammadiyah menghadapi tantangan berupa kesenjangan literasi digital, kompetisi narasi keagamaan, hoaks dan disinformasi, serta keterbatasan sumber daya manusia. Namun, era digital juga membuka peluang strategis seperti jangkauan dakwah tanpa batas geografis, efisiensi organisasi, dan pembangunan ekosistem digital terintegrasi. Penelitian ini merekomendasikan strategi komprehensif meliputi pengembangan roadmap transformasi digital, investasi SDM, pembangunan infrastruktur digital, dan penguatan keamanan siber untuk memperkuat implementasi kemuhammadiyahan di era digital.